2020
DOI: 10.1063/5.0025127
|View full text |Cite
|
Sign up to set email alerts
|

Effect of argon and oxygen gas concentration on mode transition and negative ion production in helicon discharge

Abstract: In this paper, the effect of mixing of argon and oxygen gas on the mode transition and negative ion production in the helicon discharge is investigated. In the source chamber of the experimental setup, argon–oxygen gas mixture plasma is produced by applying RF power from 100 W to 2000 W at an applied magnetic field of 0.03 T. In this experiment, the total flow rate is kept at 200 SCCM, corresponding to the working pressure of 4–5 × 10−1 Pa. The mode transition to helicon discharge is investigated by varying th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…For all cases of investigation, we keep Ψ p = 5 and 𝛾 = 15, unless mentioned otherwise. The value of Ψ s can be determined for different 𝛼 0 , following the Equation (23). For a simple electronegative plasma, the equation has a multi-valued solution in the range 1.569 < 𝛼 0 < 4.951.…”
Section: Comparing Previous Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For all cases of investigation, we keep Ψ p = 5 and 𝛾 = 15, unless mentioned otherwise. The value of Ψ s can be determined for different 𝛼 0 , following the Equation (23). For a simple electronegative plasma, the equation has a multi-valued solution in the range 1.569 < 𝛼 0 < 4.951.…”
Section: Comparing Previous Resultsmentioning
confidence: 99%
“…[12][13][14][15][16][17] The electronegative plasma sheath under different conditions has already been widely explored. [18][19][20][21][22][23] However, with the advent of fusion research, interest has grown to study the electronegative sheath with negative ion emitting wall. [5,9,24,25] It has been shown earlier [5,14,26] that if the temperature ratio of the electrons and volume negative ions exceed a value of 5 + √ 24, the sheath edge electric potential becomes multi-valued with respect to the electronegativity.…”
Section: Introductionmentioning
confidence: 99%
“…A half-helical antenna is wrapped around the source chamber to deliver the applied RF power into the system. The complete description of the system is discussed elsewhere [36,39]. After production of the plasma in the source chamber, it is allowed to expand in the expansion chamber.…”
Section: Methodsmentioning
confidence: 99%
“…They showed that regardless of whether there is a magnetic field, the metastable state is an important feature affecting ionization. The presence of a static axial component of the magnetic field also affects plasma properties [30,31], which results in a plasma anisotropy that complicates discharges. Generally, the metastable state is believed to be produced through the collisions of high-energy electrons with ground-state particles [32,33].…”
Section: Introductionmentioning
confidence: 99%